Chemical constituents from basidiomycete Basidioradulum radula culture medium and their cytotoxic effect on human prostate cancer DU-145 cells - Ryu, S.M.; Nguyen, Q.N.; Lee, S.; Kwon, H.; Kwon, J.; Lee, H.; Kwon, S.L.; Lee, J.; Hwang, B.Y.; Yim, J.-H.; Guo, Y.; Kim, J.-J.; et al. (Academic Press Inc., 2021)
Eight new naphtho[1,2-c]furan derivatives (1？8) along with six known analogues (9？14) were isolated from culture medium of the basidiomycete Basidioradulum radula. The structures of these compounds were identified using spectroscopic analysis, and their absolute configurations were resolved using X-ray diffraction, ECD, and VCD. Compounds 7 and 14 inhibited the cell viability of human prostate cancer DU-145 cells with IC50 values of 7.54 ± 0.03 μM and 5.04 ± 0.03 μM, respectively. At 8 μM, compounds 7 and 14 increased the percentage of apoptotic cells and upregulated the protein expression related to the apoptosis caspase pathways in DU-145 cells. Furthermore, the hallmarks of cells undergoing apoptosis, such as chromatin condensation, were also observed at this concentration. However, compound 7 and 14 showed no effect on the proliferation of splenocytes isolated from cyclophosphamide-induce immunosuppressed mice. ？ 2021 Elsevier Inc.